Utilization of Google Maps API in the Development of the Integrated Monitoring Information System (SIMONIT) at the Department of Transportation, Dumai City - Hadi, Nurhadi; Tri Putri, Nilda Tri Putri (Jurnal Sarjana Teknik Informatika, 2025)
This study focuses on the design and implementation of the Integrated Monitoring Information System (SIMONIT), utilizing the Google Maps API to support infrastructure management by the Department of Transportation of Dumai City. The system was developed to enable digital and integrated monitoring of various infrastructure elements such as Public Street Lighting (PSL), traffic lights, warning lights, road markings, and traffic signs. The research employs a descriptive method combining both qualitative and simple quantitative data. The findings show that the implementation of SIMONIT significantly contributes to operational efficiency, data accuracy, faster reporting, and improved transparency and accountability in public asset management. A total of 1,273 PSL points have been recorded in the system, with photo documentation available for approximately 90% and complete GPS coordinates. Additionally, the public complaint module registered 168 reports, with an 87% resolution rate and an average response time of only 1 to 2 days. This system also enhances decision-making capabilities and can serve as a reference for developing other digital public service platforms.